A case of acute septic arthritis of the hip joint caused by Panton-Valentine leukocidin-positive ST772 community-acquired methicillin-resistant Staphylococcus aureus. Issue 3 (March 2019) - Takadama, Shunsuke; Yamagishi, Yuka; Nakaminami, Hidemasa; Morishima, Takkan; Deie, Masataka; Mikamo, Hiroshige; Noguchi, Norihisa
Abstract: Acute septic arthritis (ASA) caused by Staphylococcus aureus can lead to fulminant arthritis and cause permanent joint destruction. In particular, infection caused by methicillin-resistant Staphylococcus aureus (MRSA) becomes intractable and severe owing to limitation of therapeutic drugs. Here, we report the case of a young patient with ASA without any record of overseas travel, who was infected by the Panton-Valentine leukocidin-positive Bengal-Bay clone, which is a predominant community-acquired MRSA in India.